Alcohol Abuse and Violent Crime: a Contemporary Examination and Comparison of Adult Male and Female Violent and Nonviolent Criminal Offenders - Haley, Don Randall (2000)
The focus of this study was to investigate the relationship between violent criminal activity and alcohol abuse, and to further extend the knowledge about these phenomenon which currently appear in the literature. The association between these two variables has been asserted for many years, but few definitive correlations have been established using representative data. This study sought to determine if a statistical relationship exists between alcohol abuse rates of inmates serving time in Louisiana and their convictions for violent crimes. The research design used to investigate the relationship between alcohol abuse and violent criminal behavior was non-experimental and correlational. Interviews and a questionnaire which obtained basic demographic information, criminal history parameters and self-reported alcohol consumption rates were used in conjunction with the Brief Michigan Alcoholism Screening Test (MAST) and case record reviews. A representative sample of inmates from the Louisiana Department of Public Safety and Corrections was taken using random selection. The inmate sample was subdivided into groups of either violent or nonviolent offenders for comparative purposes (n = 424; 359 adult males and 65 adult females). The model for data analysis was a cross-tabular comparison of multiple interview and questionnaire results using multiple linear regression. Six demographic variables were controlled for to eliminate extraneous variance and to determine statistically significant differences. Alcohol abuse and whether an inmate was charged with a violent crime were found to be inter-related (p = .048). When the primary offense violent crime category was regressed on inmate alcohol abuse diagnoses controlling for gender, age, race, occupation, income and educational attainment, a significant statistical interaction effect continued to be observed (p = .049)